CULTURAL REFLECTIONS IN ENGLISH AND UZBEK IDIOMS: A CROSS-LINGUISTIC ANALYSIS - Qurbonova Malohat Jalil qizi (New modern researchers: modern proposals and solutions, 2025)
This scientific article discusses cultural skills in Uzbek and English.